KOMUNIKASI INTERPERSONAL KELUARGA DALAM MENJAGA KESEHATAN MENTAL ANAK - Nurul Huda; Sri Nawangsari; Dona Putri Kasandi (Jurnal Sosial Humaniora dan Pendidikan, 2024)
In the family can support mental health, especially broken home children, communication between parents and children has many impacts, such as the development of children's emotions, character and attitude formation. The purpose of this study was to determine family communication on the mental health of broken home children. This research, using qualitative methods because the targets taken have the same characteristics, namely the family. Data validity was carried out using data source tringulation techniques. This research has interpersonal messages obtained between parent and child communication. The theory used is S-O-R Theory by conducting interviews with 4 men and 4 women aged 17-25 years old children who experienced broken homes. Data collection techniques are interviews, observation, documentation. The results of this study explain that family interpersonal communication in maintaining children's mental health is very influential for children, especially broken home children who experience mental health, because communication between parents and children is needed, therefore the important role of parents is needed so that there is no promiscuity for children.